Poor Clearance of Free Hemoglobin Due to Lower Active Haptoglobin Availability is Associated with Osteoarthritis Inflammation - Sarkar A; Monu; Kumar V; Malhotra R; Pandit H; Jones E; Ponchel F; Biswas S (Dove Medical Press, 2021)
Ashish Sarkar,1,2 Monu,1,2 Vijay Kumar,3 Rajesh Malhotra,3 Hemant Pandit,4 Elena Jones,4 Frederique Ponchel,4 Sagarika Biswas1 1Department of Integrative and Functional Biology, CSIR-Institute of Genomics and Integrative Biology, New Delhi, 110007, India; 2Academy of Scientific and Innovative Research (AcSIR), Ghaziabad, Uttar Pradesh, 201002, India; 3All India Institute of Medical Sciences, New Delhi, 110029, India; 4Leeds Institute of Rheumatic and Musculoskeletal Medicine, School of Medicine, University of Leeds, Leeds, UKCorrespondence: Sagarika BiswasDepartment of Integrative and Functional Biology, CSIR-Institute of Genomics and Integrative Biology, Near Jubilee Hall, Mall Road, New Delhi, 110007, IndiaTel +91 11-2766-2581Email sagarika.biswas@igib.res.inIntroduction: Circulating plasma proteins play an important role in various diseases, and analysis of the plasma proteome has led to the discovery of various disease biomarkers. Osteoarthritis (OA) is the most common chronic joint disease, mostly affecting people of older age. OA typically starts as a focal disease (in a single compartment, typically treated with unicompartmental knee replacement), and then progresses to the other compartments (if not treated in time, typically treated with total knee replacement). For this, identification of differential proteins was carried out in plasma samples of OA cases and compared with healthy controls. The aim of this study was to identify circulatory differentially expressed proteins (DEPs) in knee-OA patients undergoing total knee replacement or unicompartmental knee replacement compared to healthy controls and assess their role, in order to have better understanding of the etiology behind OA pathophysiology.Methods: DEPs were identified with two-dimensional gel electrophoresis (2DE) and isobaric tags for relative and absolute quantification (iTRAQ), followed by liquid chromatography with tandem mass spectrometry. Validation of DEPs was carried out using Western blot and ELISA. Posttranslational modifications were checked after running native gel using purified protein from patients, followed by detection of autoantibodies.Results: In total, 52 DEPs were identified, among which 45 were distinct DEPs. Haptoglobin (Hp) was identified as one of the most significantly upregulated proteins in OA (P=0.005) identified by both 2DE and iTRAQ. Decreased levels of Hp tetramers and increased levels of autoantibodies against Hpβ were observed in OA plasma.Conclusion: Our data suggest that poor clearance of free hemoglobin and low levels of Hp tetramers may be associated with OA pathogenesis and inflammation.Keywords: osteoarthritis, blood, haptoglobin, hemoglobin, biomarker, inflammation